FIXED-BUDGET APPROXIMATION OF THE INVERSE KERNEL MATRIX FOR IDENTIFICATION OF NONLINEAR DYNAMIC PROCESSES - Antropov, Nikita; Agafonov, Evgeny; Tynchenko, Vadim; Bukhtoyarov, Vladimir; Kukartsev, Vladislav (Journal of Applied Engineering Science, 2022)
The paper considers the identification of nonlinear dynamic processes using kernel algorithms. Kernel algorithms rely on a nonlinear transformation of the input data points into a high-dimensional space, that allow solving nonlinear problems through construction of kernelized counterparts of linear methods by replacing the inner products with kernels. One key issue of the kernel algorithms is high complexity of the inverse kernel matrix calculation. Nowadays, there are basically two approaches to this problem. The first one is based on using reduced training data sample instead of full one. In case of kernel methods, this approach could cause model misspecification, since kernel methods are directly based on training data. The second one is based on the reduced-rank approximations of the kernel matrix. Major limitation of this approach is that the rank of the approximation is either unknown until approximation is done or it is predefined by user, both of which are not so efficient. In this paper, we propose a new regularized kernel least squares algorithm based on the fixed-budget approximation of the kernel matrix. Proposed algorithm allows regulating computational burden of the identification algorithm and obtaining the least approximation error. We have shown some simulations results illustrating the efficiency of the proposed algorithm compared to other algorithms. Application of the proposed algorithm is considered on the identification problem of the input and output pressure of the pump station.
Keywords: kernel methods, nonlinear process, identification, low-rank approximation, computational efficiency